2019
DOI: 10.1177/2050313x19841825
|View full text |Cite
|
Sign up to set email alerts
|

Use of atypical antipsychotics and risk of hypertension: A case report and review literature

Abstract: Atypical antipsychotics is being considered in the treatment of “negative” symptoms of psychoses, such as schizophrenia. In this case report, we presented a case of a patient with psychiatric disorder who developed hypertension soon after starting using atypical antipsychotic. A 53-year-old woman had reported having episodes of tachycardia, nausea, headache and high blood pressure. At the time of the doctor’s appointment, the blood pressure was 210/110 mmHg. According to the patient, she made use of simvastati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 17 publications
1
7
0
1
Order By: Relevance
“…Receptors D1, D3, and D4 interact with the renin-angiotensin-aldosterone system, whereas D2 and D5 with post-ganglia presynaptic sympathetic nerves. When activated, the receptors inhibit norepinephrine production at sympathetic nerve endings, leading to increased blood pressure [25]. In this study, there was also an increase in blood pressure's mean value in the 3 rd month after giving antipsychotic drug therapy.…”
Section: Discussionsupporting
confidence: 46%
“…Receptors D1, D3, and D4 interact with the renin-angiotensin-aldosterone system, whereas D2 and D5 with post-ganglia presynaptic sympathetic nerves. When activated, the receptors inhibit norepinephrine production at sympathetic nerve endings, leading to increased blood pressure [25]. In this study, there was also an increase in blood pressure's mean value in the 3 rd month after giving antipsychotic drug therapy.…”
Section: Discussionsupporting
confidence: 46%
“…The literature on the appearance of hypertension due to antipsychotics seems to be restricted to case studies/series ( 78 , 79 ). The largest existing cohort study, comprising 284,234 individuals, showed that those with 1 year of exposure to SGAs showed only a small heightened risk of essential hypertension (Hazard Ratio, HR = 1.16, p < 0.0001), compared to those using antidepressants ( 80 ) ( Table 1 ).…”
Section: Hypertensionmentioning
confidence: 99%
“…Moreover, there does not seem to be an additive effect on blood pressure when combining antipsychotics ( 51 ). The possible small increased risk in hypertension after antipsychotic treatment probably can be attributed to antipsychotic-induced weight gain/obesity ( 81 ) and to the anti-dopaminergic effect of these agents, as all 5 dopamine receptor subtypes (D1–D5) regulate blood pressure ( 78 , 82 ).…”
Section: Hypertensionmentioning
confidence: 99%
“…36 Efek peningkatan tekanan darah setelah pasien diberikan terapi kombinasi risperidon dan klozapin tidak terjadi dapat disebabkan oleh durasi terapi yang terlalu singkat, profil farmakokinetik, dan adanya efek sinergisme farmakologi. 37,38 Mekanisme peningkatan berat badan sangat berpengaruh pada patogenesis sindroma metabolik, secara tidak langsung hambatan pada reseptor neurobiologi di otak mampu meningkatkan rasa lapar. 39 Kombinasi risperidon dan klozapin memiliki efek mutatif terhadap reseptor serotonin (5HT2C) dan LEP-2548 A/G yang menyebabkan peningkatan berat badan dalam waktu 6-16 minggu.…”
Section: Karakteristik Sosiodemografi Dan Klinikunclassified